Study of accuracy and grammatical complexity in EFL writing - Lahuerta, Ana Cristina (International Journal of English Studies, 2018)
The present study seeks to compare the writing products of EFL undergraduates using as measures accuracy and grammatical complexity. It also intends to describe the evolution of the morphological and syntactic errors as English is used by learners. A total of 100 learners of English as a foreign language participated in the study. They were divided into two groups according to their Oxford Placement Test score: group A was formed by 36 advanced students; and group B was made up of 64 upper intermediate students. Compositions were collected as the basis of this study. Results show that upper intermediate students exhibited a higher error mean in each of the error categories, namely, grammatical morphemes, lexical choice and syntax, as well as punctuation and spelling. However, an analysis of variance shows the differences between groups to be significant only in spelling errors and in punctuation errors.